Use of the virtual classroom and development of digital skills in students: Case of Peru - Dávila Morán, Roberto Carlos; López Gómez, Henri Emmanuel (Journal of the University of Zulia, 2022)
This study aimed to establish the relationship between the use of the virtual classroom and the development of digital skills in students of a Peruvian university. The research was developed under the quantitative approach, of a non-experimental correlational design, of a basic type; The sample consisted of 412 students from the Faculty of Engineering and the Faculty of Business of the North Private University, Peru. The data collection technique was the survey and the instrument was the questionnaire. The results indicate that the use of virtual classrooms obtained a moderate frequency with 42%, while digital skills achieved development in process with 40%. It is concluded that there is a moderate direct relationship between the use of virtual classrooms and the development of digital skills in students of a Peruvian university, demonstrated with Rho = .528 and p-value = 0.000 < 0.05.